(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2011)
“I had never made a direct connection between education and democracy before taking this class. (I’m actually ashamed to admit this because it now seems so obvious.)” This is only one among many similar comments from the students—all practicing teachers—whom we teach. What is it about teachers’ professional lives that so obscures the democratic mission of schools? The answer lies, at least in part, beyond school walls. Since the inception of public schools in the United States, at least three fundamental goals for them have vied for ascendency in the social imagination. One, inspired by the rhetoric of our country’s founders, particularly Thomas Jefferson, exhorts the schools to educate for a participatory democratic citizenry. Another, rooted in America’s can-do pioneer spirit and Emersonian self-reliance, urges schools to prepare economically self-sufficient and productive workers. A third harkens to the Greek notion of paidiea, educating each individual in his/her own unique way to contribute to the common good of the culture. All of these goals hold considerable merit, and there is obviously clear overlap among them. In fact, preparing students for democratic citizenship, economic viability, personal development and moral responsibility are all crucial to their future lives as adults.